Compliance of Water Closet Facilities in Mosques with Malaysian Standards, Guideline and Legislation - Mohamad Nazir, Amni Umirah (International Journal of Integrated Engineering, 2019)
A mosque often has a main prayer hall and other ancillary spaces. These spaces include water closets that provide general facilities, such as wash-hand basins, ablution areas, shower areas and water cubicles (including those for the disabled). The specifications for the design of these ancillary components are defined in various Malaysian standards and guidelines relevant to water closet design. They are namely, Malaysian Standard MS 2577: 2014 (Architecture and Asset Management of Masjid – Code of Practice), Malaysian Standard MS 2015: Part 1: 2006 (Public Toilet – Part 1: Minimum Design Criteria), Malaysian Standard MS 1184: 2014 (Universal Design and Accessibility in the Built Environment – Code of Practice, Second Revision ), JKR 1999 (Guidelines on Buildings Requirements for Disabled Persons) and UBBL: 1984 (Unit Building By-Laws – Part III: Space, Light and Ventilation). Access audit was conducted in this study to investigate the compliance of mosque water closets with these national standards and guidelines and to obtain insights into the actual situation. A five-point rating scale was developed for the access audit (1=not provided; 2=provided but below the recommendation; 3=provided and exactly as the recommendation; 4=provided but above the recommendation; 5=provided but not in the recommendation). The scores of every criterion were computed to determine the compliance percentage. The study was conducted in five mosques to assess the on-site and as-built compliance of their water closets. The results showed that compliance percentages of the studied mosques ranged from only 43% to 64%, which indicated that the provisions of water closet facilities were not fully in compliance with the stipulated national standard, guidelines and legislation due to the lack of awareness and less prioritization on the requirements for water closet facilities.